Western Europe's democratic age, 1945-1968 - Conway, Martin 1960- (Princeton University Press, 2020)
"This book provides a novel account of the decades following the Second World War in the western half of Europe through the prism of its democratisation. Previous experiences of democracy in Europe had not tended to end well; but Western Europe after 1945 witnessed the establishment of a stable, durable, and remarkably uniform model of rather conservative parliamentary democracy. This was the product of much more than the defeat of fascism and the rejection of Communism. It rested on the construction of new forms of state authority, new policies of social and economic development, and the emergence of political forces - primarily Socialism and Christian democracy - which found a common interest in the new model of democracy. It also gained the support of the people. The broad cross-class alliance which developed in much of Western Europe behind democracy after 1945 was a gradual process, but one which rested on its combination of respect for established material interests and the emergence of new and more individualist notions of citizenship. Based on a wide range of primary and secondary material from throughout Western Europe, this is not a chronological account of the post-war era, or still less a country-by-country survey; instead, it analyses Western Europe's conversion to democracy through five analytical chapters which consider its construction, its intellectual ideas, its social culture, its Socialist and Christian democratic variants, and finally the arguments about democracy which developed during the 1960s. The book concludes with an epilogue which discusses the evolution of democracy in Europe since the 1960s"--